Qualidade de vida relacionada à saúde de cuidadores familiares de indivíduos com sequela de acidente vascular encefálico - Costa, Tatiana Ferreira da (2014)
Introduction: The physical and cognitive sequelae caused by CVA compromise the functional capacity, and the independence and autonomy of the person affected by the CVA, causing changes in the dynamics of life not only of the individual affected, but also the family, especially for the main caregiver. Objectives: evaluating the health-related quality of life of family caregivers of patients with sequelae with CVA. Methods: the research was descriptive, transversal type, with a quantitative approach, held at the domicile of patients with sequelae by AVE, in the city of João Pessoa-Paraíba, in the period between the months of February and April 2013. The population of the study consisted of 136 family caregivers of patients affected by stroke. For data collection, there was used a structured instrument, contemplating closed issues relating to variables of the study and the specific measures to assess, respectively, the physical capacity of individuals with sequel by CVA, the overload and health-related quality of life among caregivers: Barthel index, Burden Interview Scale and Short Form-36. The analysis was performed using three techniques: statistical descriptive analysis and exploratory data analysis and Association through the Chi-square test and the T-test and F for comparisons of the averages. The project was submitted to the ethics committee of the Centre for Health Sciences, Federal University of Paraíba Health and approved under protocol number 0279/13 and CAAE: 13778313.3.0000.5188. Results: commitment was evidenced in almost all domains of quality of life of family caregivers, among them, those who were presented with lower average were: Pain (40.16), Mental Health (53.62) and Social Aspects (54.12). Characteristics of individuals with sequel by CVA, which is related with the domains of quality of life, one can find out that those who were below the age of 65, were married and had highest level of schooling, major averages, respectively, in the fields of Social Aspect, Emotional and Mental Health Aspects. Caregivers of people with higher level of dependency to the basic activities of daily living had lower average in the mental health field. Regarding the characteristics of the caregiver, major averages were caregivers under the age of 40 years old and married in the field, Functional Capacity, those who had a profession, on emotional aspects and those who had higher income, in the areas of mental health and vitality. There was also an association between overload and worse health-related quality of life in the areas of functional capacity, physical aspects, emotional aspects and Pain. Conclusion: the results of the study allowed understanding the different dimensions and specificities in the context of the health-related quality of life, evidencing the need for redirection of the look to public spheres for the recognition of the problems faced by the family when individuals are affected by a disabling disease, such as CVA.